2018
DOI: 10.21273/horttech04007-18
|View full text |Cite
|
Sign up to set email alerts
|

Root-zone Cooling Evaluation Using Heat Pump for Greenhouse Strawberry Production

Abstract: Ground-source heat pumps (GSHPs) have been used to chill water to facilitate cooling of ‘Natsuakari’ strawberry (Fragaria ×ananassa) grown within containers during the summer. Two types of soil containers and cooling systems have been considered. In one system, cold-water tubes were placed under as well as over the top of the soil, whereas the other cooling system used cold water passing through tubes placed under the soil and within the irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Almost commercial strawberry cultivars are June-bearing or short-day strawberry that need cool temperature (vernalization) to induce flower bud. Strawberry plants vernalized at 2 °C for 2 weeks had the highest percentage of flowering, number of inflorescences, number of flowers per inflorescence and number of flowers per plant as compared to vernalized at 4 °C [24]. [25] also indicated that cooling of the crown to 10-20°C induced flower bud differentiation of June-bearing strawberries.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Almost commercial strawberry cultivars are June-bearing or short-day strawberry that need cool temperature (vernalization) to induce flower bud. Strawberry plants vernalized at 2 °C for 2 weeks had the highest percentage of flowering, number of inflorescences, number of flowers per inflorescence and number of flowers per plant as compared to vernalized at 4 °C [24]. [25] also indicated that cooling of the crown to 10-20°C induced flower bud differentiation of June-bearing strawberries.…”
Section: Discussionmentioning
confidence: 89%
“…Literature suggests that a cost-effective IoT system can effectively automate greenhouse setup [11,13,14]. Arduino Uno is a cost-effective and farmer-friendly microprocessor that is extremely precise and efficient setup [24]. The data monitored, acquired, and gathered by these microcontrollers can result in more efficient plant growth and resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this product is made from components that are easy to find in the market as well as affordable prices and specifications that are easy to adjust. The use of technology, especially in the era of the industrial revolution 4.0, should be intensively used so that the production of cultivated plants and food can be more optimal (Cormier et al, 2020;Goodchild, K. D. Kühn, Jenkins, Burek, & Dutton, 2015;Létourneau & Caron, 2019;Moritani, Nanjo, Itou, & Imai, 2018). So that the presence of the technology can balance the productivity and efficiency of human work (Ananingtyas, Sakti, Hakim, & Lestari, 2022).…”
Section: Product Specification Informationmentioning
confidence: 99%